Perceptions derived from experiences on physical education lessons and their consequences in sport habits in non-compulsory secondary education students - F. Ruiz; M. E. García; A.I. Hernández (Asociación Española de Ciencias del Deporte, 2010)
Being conscious of the availability of free time, the type of activities which realise, the behaviours, the poses and motivations concerning the physical or sportive practise within the leisure time, as well as the demand which presents the scholarship of Almeria in Enseñanza Secundaria Post Obligatoria (ESPO), establishing distinguishing profiles according to sex, age, marital status, studies, shift of class and site of residence, is subject of the present work for investigation. Evaluate the influence that receives or that has been receiving xxx physical education received in primary school or high-school, as soon as attitudes to their parents in their leisure time concerning the physical or sportive activity realised out of the educational timetable. The data gathering has been realised with quantitative methodology by surveys (autoadministrated questionnaire with massive application -per rooms- and presence of the applicant). The assumed sample error is about ±3%, the confidence level is about 95'5%. The quantitative techniques for analysing data are made by the computer program SPSS/PC+ (v.7.52), presenting descriptive analysis of the different variables planned, like inferential analysis with the correspondent contingence tables, Pearson's index and signification level. KEY WORDS: behaviours, physical or sportive practise within the leisure time, scholarship.